Perspectives on complement and phagocytic cell responses to nanoparticles: From fundamentals to adverse reactions - Moghimi, S. Moein; Haroon, Hajira B.; Yaghmur, Anan; Hunter, A. Christy; Papini, Emanuele; Farhangrazi, Z. Shadi; Simberg, Dmitri; Trohopoulos, Panagiotis N. (Journal of controlled release, 2023)
The complement system, professional phagocytes and other cells such as Natural killer cells and mast cells are among the important components of the innate arm of the immune system. These constituents provide an orchestrated array of defences and responses against tissue injury and foreign particles, including nanopharmaceuticals. While interception of nanopharmaceuticals by the immune system is beneficial for immunomodulation and treatment of phagocytic cell disorders, it is imperative to understand the multifaceted mechanisms by which nanopharmaceuticals interacts with the immune system and evaluate the subsequent balance of beneficial versus adverse reactions. An example of the latter is adverse infusion reactions to regulatory-approved nanopharmaceuticals seen in human subjects. Here, we discuss collective opinions and findings from our laboratories in mapping nanoparticle-mediated complement and leucocyte/macrophage responses. [Display omitted] •Complement system plays multifaceted roles in nanoparticle performance.•Phagocytic cells intercepts nanoparticles in multiple ways.•The role of phagocytes, complement and contact system in hypersensitivity to nanoparticles is scrutinised.